2017
DOI: 10.1016/j.ijedudev.2016.10.002
|View full text |Cite
|
Sign up to set email alerts
|

The impact of bullying on students’ learning in Latin America: A matching approach for 15 countries

Abstract: We examine the impact of bullying on learning and non-cognitive outcomes for sixth grade students in 15 Latin America countries using data from the Third Regional Comparative and Explanatory Study (TERCE) learning survey. We apply OLS and propensity score matching to attenuate the impact of confounding factors. Matching results show that students being bullied achieve between 9.6 and 18.4 points less in math than their non-bullied peers whilst in reading between 5.8 and 19.4 lower scores, a 0.07-0.22 reduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 49 publications
4
25
0
2
Order By: Relevance
“…Several studies have shown that this fear and truancy due to bullying can lead to mental problems and lower academic achievement of students [15,39]. Supporting this evidence, previous studies have emphasized the requirements of appropriate anti-bullying programs at schools [40][41][42][43][44][45].…”
Section: Mental Health Behaviorsmentioning
confidence: 94%
See 1 more Smart Citation
“…Several studies have shown that this fear and truancy due to bullying can lead to mental problems and lower academic achievement of students [15,39]. Supporting this evidence, previous studies have emphasized the requirements of appropriate anti-bullying programs at schools [40][41][42][43][44][45].…”
Section: Mental Health Behaviorsmentioning
confidence: 94%
“…Victimized students fear being at school and are more likely to miss school, play truant, avoid school activities and show poor academic performance [15][16][17]. Results from these studies have highlighted on the importance of promoting a safe and bully-free learning environment for better educational development of students.…”
Section: Introductionmentioning
confidence: 99%
“…5 Using matching techniques to obtain matched sub-samples to isolate observables has been used to study the private school effect (Chudgar and Quin, 2012) and also for the learning gap related to school violence (Delprato et al, 2017). A formal version of this approach is Coarsened Exact Matching (CEM) where the balance between the treated and control groups is chosen ex-ante by the research (see Iacus et al, 2011).…”
Section: Appendix B: Estimates Accounting For Unobservablesmentioning
confidence: 99%
“…The increasing prevalence of this type of violence in schools on this continent shows it is becoming more systematic and accepted as the norm in social relationships and conflict resolution between children and adoelscents 17 . Furthermore, there are gaps in the literature, in particular in terms of the role played by students identified as aggressors in bullying situations, as most studies focus on the victims and the experience they report 18,19 .…”
Section: Introductionmentioning
confidence: 99%